Pipelines and permafrost : science in a cold climate - Williams, Peter J. (Peter John), 1932- (Carleton contemporary, 1986)
Emphasizes scientific flaws in the proposals for pipelines in cold places. Includes chapters on the trans-Alaska and Alaska Highway pipelines.